2003
DOI: 10.1016/s1534-5807(03)00238-7
|View full text |Cite
|
Sign up to set email alerts
|

Ent3p Is a PtdIns(3,5)P2 Effector Required for Protein Sorting to the Multivesicular Body

Abstract: PtdIns(3,5)P(2) is required for cargo-selective sorting to the vacuolar lumen via the multivesicular body (MVB). Here we show that Ent3p, a yeast epsin N-terminal homology (ENTH) domain-containing protein, is a specific PtdIns(3,5)P(2) effector localized to endosomes. The ENTH domain of Ent3p is essential for its PtdIns(3,5)P(2) binding activity and for its membrane interaction in vitro and in vivo. Ent3p is required for protein sorting into the MVB but not for the internalization step of endocytosis. Ent3p is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
113
0
16

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(137 citation statements)
references
References 47 publications
(4 reference statements)
8
113
0
16
Order By: Relevance
“…In a similar vein to that described for the FAPP1 PH domain and PtdIns4P, we have been unable, with the vesicle-based techniques described above, to detect PtdIns(3,5)P 2 specificity for two interesting classes of protein: mammalian Vps24p [22] (a component of the ESCRT III complex), and Ent3p/Ent5p from S. cerevisiae [11,68]. In both of these cases, the primary evidence in support of PtdIns(3,5)P 2 specificity came from studies in which the phosphoinositide was studied in isolation.…”
Section: Ptdins(35)p 2 -Specific Binding Proteinsmentioning
confidence: 57%
See 2 more Smart Citations
“…In a similar vein to that described for the FAPP1 PH domain and PtdIns4P, we have been unable, with the vesicle-based techniques described above, to detect PtdIns(3,5)P 2 specificity for two interesting classes of protein: mammalian Vps24p [22] (a component of the ESCRT III complex), and Ent3p/Ent5p from S. cerevisiae [11,68]. In both of these cases, the primary evidence in support of PtdIns(3,5)P 2 specificity came from studies in which the phosphoinositide was studied in isolation.…”
Section: Ptdins(35)p 2 -Specific Binding Proteinsmentioning
confidence: 57%
“…Phage display was used to identify mVps24p as a protein that binds to immobilized biotinylated PtdIns(3,5)P 2 [22]. Lipid overlay/dot-blot approaches provided the initial suggestion that the ENTH domains of Ent3p and Ent5p bind PtdIns(3,5)P 2 [11,68]. Both sets of studies also employed vesicle sedimentation approaches using 5% (mole/mole) phosphoinositide in a reasonable lipid background.…”
Section: Ptdins(35)p 2 -Specific Binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single ent3⌬ deletion strain does not display the defects in MVB sorting observed in ent3-1 mutant cells. This suggested that the point mutation in the ENTH domain of Ent3p found in ent3-1 mutant cells had a dominant effect on MVB protein sorting and that there could be additional PtdIns(3,5)P 2 effectors required for MVB sorting (Friant et al, 2003). In our query for ENTH domain proteins redundant to Ent3p, we identified Ent5p.…”
mentioning
confidence: 96%
“…The ENTH domain promotes membrane recruitment by binding phosphoinositides . We have recently reported that Ent3p is a specific PtdIns(3,5)P 2 effector involved in protein sorting at the MVB in yeast (Friant et al, 2003). Analysis of yeast mutants unable to synthesize PtdIns(3,5)P 2 , such as fab1, vac7, and vac14, revealed that this phospholipid is also required for sorting ubiquitinated cargoes into the MVB (Bonangelino et al, 1997;Odorizzi et al, 1998;Reggiori and Pelham, 2001;Dove et al, 2002).…”
mentioning
confidence: 99%